STRATEGI KOMUNIKASI HUMAS PT ANGKASA PURA I BANDARA I GUSTI NGURAH RAI BALI DALAM MENSOSIALISASIKAN PENCEGAHAN VIRUS COVID-19 (E-Jurnal Medium, 2022)
Following the outbreak of the COVID-19 virus pandemic, PR have promoted intensive socialization to provide information between organizations and their communities. The purpose of this study was to determine the PR communication strategy of PT Angkasa Pura I Gusti Ngurah Rai in providing information dissemination to the public about the COVID-19 virus. This study uses an analysis of communication strategies through socialization based on planning, namely socialization carried out on the basis of a sustainable and systematic plan. The results of the study indicate that PR of PT. Angkasa Pura I I Gusti Ngurah Rai Airport using various social media platforms to inform, increase knowledge and community activity regarding the prevention of the COVID-19 virus at airports, socialization 'Fly Again', followed the policies issued by the government and evaluations with companies.